2016
DOI: 10.1095/biolreprod.116.138719
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Coating Beta-Defensin 126 Is a Dissociation-Resistant Dimer Produced by Epididymal Epithelium in the Bovine Reproductive Tract

Abstract: Beta-defensins are innate immune molecules, often described as antimicrobial peptides because of their bactericidal activity and are now known to have diverse additional functions, including cell signaling, chemoattraction, immunoregulation, and reproduction. In humans and primates, beta-defensin 126 has been shown to regulate the ability of sperm to swim through cervical mucus and to protect sperm from attack by the female immune system during transit toward the oviduct. Bovine beta-defensin 126 (BBD126) is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…A custom monoclonal antibody specific for BBD126 (α-BBD126 antibody [Ab]) was ordered from GeneScript, and generated as described by Narciandi et al [ 29 ]. Briefly, five BALB/c mice were inoculated with a 14-amino acid chemically produced peptide (RNGERVINPPTGMC).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A custom monoclonal antibody specific for BBD126 (α-BBD126 antibody [Ab]) was ordered from GeneScript, and generated as described by Narciandi et al [ 29 ]. Briefly, five BALB/c mice were inoculated with a 14-amino acid chemically produced peptide (RNGERVINPPTGMC).…”
Section: Methodsmentioning
confidence: 99%
“…Cattle represent an excellent model in which to study issues of male fertility due to the large national databases available, the high number of progeny per sire, and the consequent high confidence associated with fertility estimates. BBD126 has been identified as an epididymal-specific protein that is secreted in the cauda epididymis of the bull [ 29 ]. However, neither its distribution on sperm nor its potential reproductive role has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…In men, variation in the bd126 sequence contributes to subfertility (Tollner et al, 2011) while the BD126 peptide has been reported to mediate sperm binding to the oviductal epithelium (Tollner et al, 2008). Our group has reported bovine beta-defensin 126 (BBD126) to be extensively expressed in the reproductive tract of the bull with preferential protein expression in the cauda epididymis (Narciandi et al, 2011) and on sperm (Narciandi et al, 2016) with similar binding patterns on the sperm surface to macaque. Beta-defensin 126 increases the net negative charge on sperm (Tollner et al, 2012), increases sperm motility, mucus penetration in vitro (Fernandez-Fuertes et al, 2016) as well as sperm binding to oviductal epithelium in vitro (Lyons et al, 2018).…”
Section: Sperm Communication and Interaction With The Female Tractmentioning
confidence: 99%
“…Of note, except for HBD2 and 3, HBD1 is expressed in the human testicular germ‐line in a consistent manner (Com et al, ). In bovine caudal epididymal and vas deferens epithelial cells, defensin β 126 (DEFB126) is associated with antimicrobial peptides involved in sperm motility (Fernandez‐Fuertes et al, ), cell signaling, chemoattraction, immunoregulation (Narciandi et al, ), and sperm binding to the oviductal epithelium (Lyons et al, ). In human studies, incubation of sperm with defensin improved sperm motility and pregnancy rate (Zupin et al, ).…”
Section: Testicular Immune Mechanismmentioning
confidence: 99%